Korupsi dan Keputusan Perusahaan untuk Ekspor: Bukti dari Indonesia - Vioni Monica (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2022)
Trade liberalization is an excellent opportunity for many firms in a country to export their products. For several years, there have been continuous discussions over what factors influence a company's decision to export. One of the essential factors that companies consider when deciding to export or not is the institutional environment, such as corruption. This study investigates the corruption's impact on firms concerning the export markets. Specifically, this study argues that corruption has a grease effect on the economy and may increase the probability of exporting directly or indirectly. The model's propositions are tested using a comprehensive dataset covering over 2,700 companies in Indonesia in 2009 and 2015 by adopting the probit and logit method. The cross-section and panel regressions confirm that firms are more likely to become exporters if they perceive higher levels of corruption in their home regions. In addition, the intensity of their exporting operations is related to business characteristics such as the firm's age, size, foreign ownership, and access to foreign technologies.